Design, Model & Planning of Prosumer Microgrid for MNS UET Multan Campus - Haseeb javed (Sir Syed University Research Journal of Engineering and Technology, 2021)
The goal of this study is to provide a model and conceptual design for a prosumer campus microgrid that will help the university campus economically. The proposed model is based on solar PV installation at department rooftop for the campus of Muhammad Nawaz Sharif University of Engineering and Technology's in Multan, Pakistan. This study indicates that a 3,196-kW grid-connected solar photovoltaic system may generate enough electrical power to meet consumption, reducing grid reliance and minimizing energy from grid supply. This study also includes an economical and financial analysis of the proposed system based on various assumptions. PVSol Software was used to conduct a solar potential study and design of the site. Our study and analysis revealed that our suggested PV model can create 3,196.53 kWh of PV energy (DC), which is about 81.6 percent of the yearly consumption of our chosen site of 3,784.56 kWh.